Effects of biochar applications on soil fertility and growth performance of Hevea brasiliensis seedlings / Mohamad Faris Mohd Ibrahim - Mohd Ibrahim, Mohamad Faris (Faculty of Plantation and Agrotechnology, 2015)
The experiment was carried out to study the effect s of rice husk biochar (RHB) on soil nutrient and growth performance of rubber seedlings RRIM 3001. Biochar was produced by pyrolysis after which it was applied as a soil amendment. This experiment was carried out for three months (85 days) in a greenhouse of UiTM Malacca, Jasin Campus. The control treatment in this experiment is TO = 7g NPK Green (standard fertilization practices). The Complete Randomized Design (CRD) is used with consist of four application rate of biochar (Tl = 5 t ha⁻¹ RHB, T2 = 10 t ha⁻¹ T3 = 15 t ha⁻¹ RHB, and T4 = 20 t ha⁻¹ RHB) and applied with standard fertilization practices. Observation started from the growth of scion which is two weeks after planting bud stumps in polybag. This experiment will help the farmer and the company of rubber plantation get the high growth performance of rubber seedlings. In this study, the treatment that applied lowest rate of biochar is significant different in term of plant height, stem diameter and number of leaves.